Nutrition Education Through Contextual Media in the Banjar Language: Efforts to Strengthen Nutrition Literacy in Elementary Schools: Indonesia - Hamidah, Jamiatul; Paramitha, Dewi Setya; Rahayu, Suci Fitri; Fatimah, Siti (LPPM UMRI, 2025)
This community service activity aims to improve the nutritional literacy of elementary school students through contextualized nutritional education using media in the Banjar language. The activity involves a team of interdisciplinary lecturers from Muhammadiyah University Banjarmasin, classroom teachers, and parents of students from two partner schools, namely SDN Pangeran 3 and SDN Sungai Miai 10 Banjarmasin. The implementation method consisted of initial observation, development of educational media in the form of digital pocket books, implementation of three counseling sessions, as well as mentoring and evaluation. The counseling material covered types of nutritious foods and the benefits of nutrients such as carbohydrates, proteins, vitamins, and minerals, delivered through games and reflective discussions. The evaluation was conducted using pre-test and post-test questions, with descriptive analysis and Wilcoxon tests. The results showed a significant increase in students' nutritional knowledge, from an average score of 58.3 to 84.7, as well as a change in consumption behavior towards a more positive direction. Local culture-based educational media proved to be effective in building students' understanding and engagement, as well as supporting the sustainable success of the MBG program. This activity produced a holistic nutritional education model that is replicable in other schools.